Diglossi i moderne arabisk skønlitteratur - Moestrup, Elisabeth A. (Passage - Tidsskrift for litteratur og kritik, 2009)
Elisabeth A. Moestrup: “Diglossia in Modern Arabic Fiction” This article discusses the phenomenon of diglossia as it is encountered in two recent works by the contemporary authors, Yusef Fadel from Morocco and Rashid al-Daif from Lebanon, Fadel and al-Daif each applies their own experimental way of negotiating the reality of diglossia and all that it entails. The article also looks into Dan Diner’s Lost in the Sacred in which he ascribes the ailments of the Arab world to among other things the failure to modernise the state of the language; as it looks into Sidney Pollock’s article about linguistic homogenization globally and Arabic’s place in this.